Descriptive Study of the Outdoor Learning Environment on Children’s Play Comfort - Munawarah Munawarah; Nur Kholiq Afandi; Sri Ratih (Sekolah Tinggi Agama Islam Sumatera Medan, 2026)
This study was motivated by the importance of outdoor learning environments in supporting the play comfort of young children, while the use of outdoor spaces in Islamic Early Childhood Education institutions often focuses more on providing facilities than on the quality of children’s play experiences. This study aims to describe how the outdoor learning environment at TK ABA 2 Sandaran plays a role in creating a comfortable play environment for children. The method used is descriptive qualitative research with data collection techniques through observation, interviews, and documentation. Data were analyzed using an interactive model through the stages of data reduction, data presentation, and drawing conclusions. The results of the study indicate that the outdoor environment at TK ABA 2 Sandaran is capable of supporting children’s play comfort through the utilization of natural elements such as trees, soil, and open spaces, which provide freedom of movement, a sense of psychological safety, as well as motor and social stimulation. Furthermore, an open-environment-based learning approach also encourages children’s creativity, exploration, and social interaction in a more active manner. The implications of this study underscore the importance of optimizing the outdoor environment as a living laboratory that supports the holistic development of young children.